International students in Hungarian higher education - Vincze, Szilvia; Bács, Zoltán (Applied Studies in Agribusiness and Commerce, 2020)
Overall, higher education in Hungary is popular with students from abroad, even if there are significant differences in terms of its structure. The ever-faster increase in the annual headcount of the international student body serves as proof to this statement. The expansion of the size of the body of international students is of special importance in higher education since in 2016 the Hungarian government set the objective of having 40,000 international students by 2023 (EMMI, 2016).Numerous studies have been published on this topic, usually focusing on specific issues, including, for example, the countries from which we receive most of the students, the most popular majors, possible economic advantages due to the presence of a great number of international students, and how internationalization takes place in higher education in Hungary.  By means of processing data published by the Hungarian Educational Authority [Oktatási Hivatal], this paper aims to present the changes in the number of international students in Hungary over the past ten years. This also includes the discussion of the structure of these changes related to a variety of issues such as relations, types of institutions and their ownership, levels and types of programs, as well as gender proportions. However, even with this effort, the officially available statistics are suitable for presenting a properly detailed assessment of the situation only to a limited extent.JEL code: I23